Screening for antibiofilm effect of antibacterial peptide pam-5 on clinical strain of multidrug-resistant pseudomonas aerugin - Wong, Li Chik (2022)
Biofilm represents a major resistant mechanism in many pathogenic bacteria. Pseudomonas aeruginosa (P. aeruginosa) is known as one of the notorious bacteria associated with biofilm-mediated antibiotic resistance, leading to prolonged hospitalization and treatment. In recent years, many studies have focused on the use of antimicrobial peptides (ABPs) as an alternative antibacterial agent against resistant bacteria, including biofilm-producing bacteria. A novel ABP named PAM-5 was previously reported for its promising antibacterial effect on a spectrum of planktonic pathogenic bacteria. However, the effect of PAM-5 on biofilm-grown bacteria has yet to be elucidated. Therefore, in this study, the ability of PAM-5 to inhibit biofilm formation as well as to eradicate of mature biofilm formed by a clinical isolate of multidrug resistant (MDR) P. aeruginosa (1894170) was evaluated. Using microtiter based biofilm inhibition assay, a clinically isolated MDR P. aeruginosa was treated with PAM-5 at concentrations ranging from 4 µg/ml to 512 µg/ml. The amount of biofilm from the treated bacteria was quantified by crystal violet staining. For biofilm eradication, MDR P. aeruginosa was grown in microtiter plate for 48 hours to establish mature biofilm, followed by peptide treatment at the same range of concentrations. Upon PAM-5 treatment, the biofilm mass was quantified by crystal violet staining while the metabolic activity of the biomass was investigated via MTT assay. From this study, PAM-5 was shown to inhibit > 50% MDR P. aeruginosa biofilm formation at 16 µg/ml and the inhibition effect increased in a dose-dependent manner. On the other hand, only 8 µg/ml of PAM-5 was required to eradicate >50% of the mature biofilm as well as the metabolic activity of the biofilm-embedded bacteria, in which PAM-5 was able to reduce the viable biofilm-embedded bacteria in a dose-dependent manner. In conclusion, PAM-5 could inhibit biofilm formation, eradicate mature biofilm, and kill biofilm embedded cells of clinical strain of MDR P. aeruginosa.